Age limits and eligibility conditions for care, extended care and leaving care support for young people in care and care leavers: the case for cross-national analysis - Robbie Gilligan (Scottish Journal of Residential Child Care)
Greater awareness internationally of the special needs and circumstances of young people leaving care settings has led to growing policy interest and innovation in recent years. This paper draws attention to a small sample of policy approaches and developments in certain jurisdictions in this area. The case is argued for the value of a cross national comparative approach in studying provision for care leavers. Potential elements of a framework for analysing relevant policy are discussed. An invitation is extended to join a continuing international 'conversation' on the themes covered in the paper.